A Compact, Bistatic Antenna System with Very High Interport Isolation for 2.4 GHz In-Band Full Duplex Applications. (16th January 2021) - Nawaz, Haq; Shoaib, Nosherwan; Niazi, Ahmad Umar; Chaudhry, Shabbir Majeed
Abstract : This paper presents a compact, dual polarized bistatic (two closely spaced transmit and receive radiators) patch antenna with excellent interport isolation performance. The presented antenna system employs differential receive mode operation for the cancellation of self-interference (SI) to achieve very high interport isolation for 2.4 GHz in-band full duplex (IBFD) applications. The presented antenna is based on two closely spaced radiators and a simple 3 dB/180° coupler for differentially excited receive mode operation. The 3 dB/180° coupler performs as a passive self-interference cancellation (SIC) circuit for the presented antenna. The small form-factor structure is realized through via interconnections between the receiving patch and SIC circuit. The prototype of the presented antenna characterizes better than 105 dB peak interport isolation. Moreover, the recorded interport isolation is more than 90 dB and 95 dB within 60 MHz and 40 MHz bandwidths, respectively. The measured gain and cross-polarization levels reflect superior radiation performance for the validation model of the proposed antenna. The presented antenna offers DC interport isolation too, which is required for active antenna applications. The novelty of this work is a compact (small form-factor) antenna structure with very high peak interport isolation along with wider SIC bandwidth as compared to previously reported antennas for full duplex applications.